2008
DOI: 10.2220/biomedres.29.9
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of put A gene in Helicobacter pylori colonization in the stomach and motility

Abstract: H. pylori is a gram-negative bacterium associated with gastric inflammation and peptic ulcer and considered a risk factor for gastric cancer in its natural habitat. However, the energy metabolism of H. pylori in the stomach remains to be clarified. H. pylori shows rather high respiratory activity with L-proline and significantly large amounts of L-proline are present in the gastric juice from H. pylori infected patients. We constructed a disrupted mutant of the put A gene, which encodes the proline utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 36 publications
0
43
1
Order By: Relevance
“…In S. meliloti, a DputA strain has a weakened ability to form root colonies [35] and, moreover, strains complemented with additional copies of putA are more competitive at establishing a symbiotic relationship with alfalfa [36,37]. The Put system has also been linked to infectivity in both Helicobacter hepaticas and Helicobacter pylori [28,29,38], and the Put system plays a role in regulating the cell cycle within Ehrlichia chaffeensis [39]. Our data demonstrate that PutA and PutR are also required for B. abortus to infect animals ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In S. meliloti, a DputA strain has a weakened ability to form root colonies [35] and, moreover, strains complemented with additional copies of putA are more competitive at establishing a symbiotic relationship with alfalfa [36,37]. The Put system has also been linked to infectivity in both Helicobacter hepaticas and Helicobacter pylori [28,29,38], and the Put system plays a role in regulating the cell cycle within Ehrlichia chaffeensis [39]. Our data demonstrate that PutA and PutR are also required for B. abortus to infect animals ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Channeling in PutA may be particularly beneficial for bacteria that have adapted to use proline as a fuel source. One example is H. pylori, which utilizes proline as a preferred energy source in the gut environment, where proline levels in the gastric juice of infected patients are 10-fold higher compared to uninfected individuals (4,38). Also, channeling segregates the P5C produced by proline catabolism from the proline biosynthetic pathway, which also uses P5C as an intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, through comparative analyses among several S. enterica serovars, it has been suggested that a relationship between swarming and intestinal colonization must exist in this bacterial species (32). Likewise, swarming is known to be important for the virulence of other bacterial pathogens, such as Proteus mirabilis, Helicobacter pylori, Vibrio parahaemolyticus, and Campylobacter jejuni (43,44,51,57). In addition, it has been reported that the RecA protein is necessary for the swarming motility of E. coli, since recA mutants of this species do not swarm (28).…”
Section: S Enterica Recao6869 Mutants Do Not Swarmmentioning
confidence: 99%